Preface to Russian translation (2012. Forthcoming): Dobbin F. 1994. Forging Industrial Policy: The United States, Britain, and France in the Railway Age. Cambridge [England], NY: Cambridge University Press - Вадим Валерьевич Радаев (Journal of Economic Sociology, 2012)
Detailed description in the text